Structure Elucidation of Helical Aromatic Foldamer–Protein Complexes with Large Contact Surface Areas. Issue 47 (30th July 2019) - Reddy, Post Sai; Langlois d'Estaintot, Béatrice; Granier, Thierry; Mackereth, Cameron D.; Fischer, Lucile; Huc, Ivan
Abstract: The development of large synthetic ligands could be useful to target the sizeable surface areas involved in protein–protein interactions. Herein, we present long helical aromatic oligoamide foldamers bearing proteinogenic side chains that cover up to 450 Å 2 of the human carbonic anhydrase II (HCA) surface. The foldamers are composed of aminoquinolinecarboxylic acids bearing proteinogenic side chains and of more flexible aminomethyl‐pyridinecarboxylic acids that enhance helix handedness dynamics. Crystal structures of HCA‐foldamer complexes were obtained with a 9‐ and a 14‐mer both showing extensive protein–foldamer hydrophobic contacts. In addition, foldamer–foldamer interactions seem to be prevalent in the crystal packing, leading to the peculiar formation of an HCA superhelix wound around a rod of stacked foldamers. Solution studies confirm the positioning of the foldamer at the protein surface as well as a dimerization of the complexes. Abstract : Superhelical complexes form in the solid state between a stack of helical aromatic foldamers and an array of proteins. In individual protein–foldamer complexes, interactions were shown to extend over an area exceeding 400 Å 2 by X‐ray crystallography and solution NMR studies (see figure).